Conceptual diversity, moderators, and theoretical issues in quantitative studies of cultural capital theory. Issue 5 (20th October 2017) - Tan, Cheng Yong
Abstract: The present study reviewed quantitative empirical studies examining the relationship between cultural capital and student achievement. Results showed that researchers had conceptualized and measured cultural capital in different ways. It is argued that the more holistic understanding of the construct beyond highbrow cultural consumption must be balanced against the threat to conceptual clarity. The review also showed that cultural capital effects on student achievement were not a singular phenomenon. Rather, they were moderated by student, family, school, and country-level sociocultural factors with significant theoretical implications. The nexus of relationships among cultural capital indicators, moderators, and student achievement, and the theoretical issues involved can be used to inform future research in the testing of a more complete theory of Bourdieu's cultural capital theory. Abstract :